Synthesis of Cu‐ZnO/Polyacrylic Acid Hydrogel as Visible‐Light‐Driven Photocatalyst for Organic Pollutant Degradation. Issue 1 (5th January 2022) - Iqbal, Shahid; Javed, Mohsin; Qamar, Muhammad Azam; Bahadur, Ali; Fayyaz, Muhammad; Akbar, Ali; Alsaab, Hashem O.; Awwad, Nasser S.; Ibrahium, Hala A.
Abstract: The present study illustrates the production of Cu‐doped ZnO nanocomposite with polyacrylic acid (PAA) microgel for the degradation of a coloured pollutant under sunlight. From 1 to 20 % Cu was doped into ZnO nanostructure (1–20 % Cu doped‐ZnO NPs) by the co‐precipitation method and applied for photocatalytic dye degradation. The 15CuZnO NPs exhibited the best dye degradation under sunlight. The 15CuZnO NPs were incorporated with PAA microgel through inverse phase polymerization under N2 gas atmosphere to yield the objective nanocomposite (PAA/CuZnO NC). The yielded composite showed an extreme rise in photocatalytic efficiency and completely mineralized MB in 60 minutes. The prepared composite showed better degradation of methylene blue than Cu‐doped ZnO nanoparticles under UV‐vis light radiation. The stability of PAA/CuZnO NC for photodegradation of dye was verified by a recycling experiment of the composite. Abstract : Cu doped ZnO nanoparticles were incorporated into Polyacrylic acid (PAA) for the formation of unique PAA/15‐CuZnO nanocomposite. The nanocomposite completely mineralized methyl blue dye (MB) in 60 min. under solar light. The fabricated PAA/15‐CuZnO nanocomposite demonstrated better degradation of MB than Cu‐ZnO nanoparticles under UV‐vis light. The fabricated PAA/15‐CuZnO nanocomposite displayed remarkable stability even after the 5 th recycle.